Improvement of Forehand Smash Shots in Table Tennis Through Drill Smash Training of PJKR STKIP Darussalam Cilacap Students - Dian Imam Saefulah; Kusmiyati Kusmiyati; Banowo Cahyadi (International Journal of Science and Applied Science: Conference Series, 2021)
The purpose of this research is to find out the increase in forehand smash strokes in table tennis games through drill smash drills. The method in this research uses experimental research methods. The population in the study were all male students of PJKR STKIP Darussalam Cilacap. Meanwhile, the sample consisted of 20 students. The number of samples was divided into 2 groups, namely 10 students in the experimental group and 10 students in the control group which was carried out using the Ordinal Pairing technique. The instrument used in this study was the table tennis smash forehand test. The research data were analyzed using the Variance Analysis Test technique with a significant level of 0.05. The results of this study indicate that there is an effect of drill smash training on Smash Forehand Shots where Fcount = 12,532 > Ftable 0.05 (1:18) = 4.41.